Einleuchten : Will, Vorstel & Simul in HH. - Szeemann, Harald (Hamburg : Deichtorhallen, 1989)
Andre, Carl ; Anselmo, Giovanni ; Baechler, Donald ; Baselitz, Georg ; Beuys, Joseph ; Boltanski, Christian ; Buren, Daniel ; Carroll, Lawrence ; Darboven, Hanne ; De Cordier, Thierry ; Deutsch, David ; Disler, Martin ; Dokoupil, Jiri Georg ; Etienne-Martin ; Flavin, Dan ; Förg, Günther ; Genzken, Isa ; Gober, Robert ; Grünfeld, Thomas ; Hsu, Tishuan ; Judd, Donald ; Kawara, On ; Kelly, Ellsworth ; Klingelhöller, Harald ; Laib, Wolfgang ; Leibowitz, Cary S. ; LeWitt, Sol ; Long, Richard ; Lüscher, Ingeborg ; Merz, Gerhard ; Merz, Mario ; Merz, Marisa ; Mucha, Reinhard ; Nauman, Bruce ; Neuhaus, Max ; Noland, Cady ; Quentel, Holt ; Rabinowitch, David ; Rabinowitch, Royden ; Rückriem, Ulrich ; Ryman, Robert ; Serra, Richard ; Sonnier, Keith ; Spitzer, Serge ; Toroni, Niele ; Trockel, Rosemarie ; Tuttle, Richard ; Twombly, Cy ; Vercruysse, Jan ; Verjux, Michel ; Vermeiren, Didier ; Biola, Bill ; Wallinger, Mark ; Weiner, Lawrence ; West, Franz ; Whiteread, Rachel ; Zeniuk, Jerry ; Zitko, Otto
Einleuchten : Will, Vorstel & Simul in HH, Deichtorhallen, Hamburg, 11. November 1989 bis 18. Februar 1990
boek